Corrigendum to the author’s name of Teguh WijayaMulya (2006 - 2016) - Teguh WijayaMulya (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
Corrigendum to the author’s name of Teguh WijayaMulya (2006 - 2016)